The more, the better? Behavioral and neural correlates of frequent and infrequent vowel exposure. Issue 5 (31st May 2017) - Tsuji, Sho; Fikkert, Paula; Minagawa, Yasuyo; Dupoux, Emmanuel; Filippin, Luca; Versteegh, Maarten; Hagoort, Peter; Cristia, Alejandrina
Abstract: A central assumption in the perceptual attunement literature holds that exposure to a speech sound contrast leads to improvement in native speech sound processing. However, whether the amount of exposure matters for this process has not been put to a direct test. We elucidated indicators of frequency‐dependent perceptual attunement by comparing 5–8‐month‐old Dutch infants' discrimination of tokens containing a highly frequent [hɪt‐he:t] and a highly infrequent [hʏt‐hø:t] native vowel contrast as well as a non‐native [hɛt‐hæt] vowel contrast in a behavioral visual habituation paradigm (Experiment 1). Infants discriminated both native contrasts similarly well, but did not discriminate the non‐native contrast. We sought further evidence for subtle differences in the processing of the two native contrasts using near‐infrared spectroscopy and a within‐participant design (Experiment 2). The neuroimaging data did not provide additional evidence that responses to native contrasts are modulated by frequency of exposure. These results suggest that even large differences in exposure to a native contrast may not directly translate to behavioral and neural indicators of perceptual attunement, raising the possibility that frequency of exposure does not influence improvements in discriminating native contrasts.